PATTERNS OF EUTECTIC ALLOYS RUNNING PROCESS - Кіндрачук, М.; Шевченко, О.; Перро, Д.; Подлєсний, В. (Science-based technologies, 2010)
The results of research running process iron-based alloys with eutectic structure type. A mechanism and optimization running methods carbon steels and eutectic alloys proposed.